Decorated sculpture of Nandi - Temples of India Project Team (Jio Institute, 2024)
The magnificently decorated sculpture of Nandi, positioned in front of the platform and oriented towards the mulaprasada (main temple), is truly impressive. Particularly notable is the hump of Nandi, adorned with an intricately coiled serpent, which gracefully encircles the hump, adding to the sculpture's beauty.